The zebrafish Multivariate Concentric Square Field: A Standardized Test for Behavioral Profiling of Zebrafish (Danio rerio) - Vossen, Laura E.; Brunberg, Ronja; Rådén, Pontus; Winberg, Svante; Roman, Erika (Frontiers in Behavioral Neuroscience, 2022)
The zebrafish (Danio rerio) is an important model organism in the study of the neurobiological basis of human mental disorders. Yet the utility of this species is limited by the quality of the phenotypical characterization tools available. Here, we present a complex testing environment for the quantification of explorative behavior in adult zebrafish, the zebrafish Multivariate Concentric Square Field (zMCSF), adapted from the rodent equivalent that has been used in >40 studies. The apparatus consists of a central open area which is surrounded by a dark corner with a roof, corridors, and an inclined ramp. These areas differ in illumination, water depth, and are sheltered or exposed to different degrees. We quantified behavior of male and female wild-caught and AB strain zebrafish in the zMCSF (day 1) and cross-validated these results using the novel tank diving test (day 2). To assess the effect of repeated testing, AB zebrafish we tested a second time in both tests one week later (on day 7 and 8). We detected strong differences between the strains, with wild zebrafish swimming faster and spending more time in the corridors and on the ramp, while they avoided the open area in the center. AB zebrafish were less hesitant to enter the center but avoided the ramp, and often left one or more zones unexplored. No major sex differences in exploratory behavior were detected in either strain, except for a slightly higher velocity of AB males which has been reported before. Importantly, the zMCSF was largely resilient to repeated testing. The diving test revealed only one difference confined to one sex; wild females paid more visits to the top third than AB females. In isolation, this finding could lead to the conclusion that wild zebrafish are more risk-taking, which is incorrect given this strain’s avoidance of open areas. To conclude, our results suggest that the zMCSF presents a sophisticated behavioral tool that can distinguish between different magnitudes and types of risk, allowing the user to create an intricate behavioral profile of individual adult zebrafish.